Trans-fatty acids and mortality in patients referred for coronary angiography: the Ludwigshafen Risk and Cardiovascular Health Study - Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (European heart journal, 2016)
Aims: Trans-fatty acids (TFAs) are generated by the food industry and also occur naturally in trace amounts in dairy products. For the latter, beneficial health effects have been claimed, while there are numerous reports about TFA of industrial origin being hazardous to human health. Therefore, we aimed to investigate the association of TFA with mortality in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. Methods and results: The fatty acid composition of erythrocyte membranes was analysed using the HS-Omega-3 Index® methodology in 3259 participants of the LURIC study at baseline. During a median of 10.0 years of follow-up, a total of 975 (29.9%) study participants died, 614 (18.8%) from cardiovascular causes including 254 (7.8%) sudden cardiac deaths (SCDs). Association of TFA with clinical outcome was investigated with Cox proportional hazards regression. Total TFAs were inversely associated with mortality due to cardiovascular causes or SCD. This was mainly driven by the naturally occurring TFA C16:1n-7t (trans-palmitoleic acid). The reduced risk of SCD associated with C16:1n-7t persisted after multivariate adjustment with a hazard ratio of 0.63 (0.46-0.86) for the third tertile compared with the first tertile. There was no association of any TFA subgroup with an increased risk of adverse outcomes. Conclusions: In contrast to previous findings, the low concentrations of total TFAs found in LURIC were inversely associated with adverse cardiac outcomes. While the naturally occurring TFA C16:1n-7t was associated with reduced risk, no increased risk was found for industrially produced TFAs.
Gesehen am 08.04.2019
Online publish-ahead-of-print 22 September 2015